Discovery of nitazoxanide-based derivatives as autophagy activators for the treatment of Alzheimer's disease - Xiaokang Li; Jian Lu; Yixiang Xu; Jiaying Wang; Xiaoxia Qiu; Lei Fan; Baoli Li; Wenwen Liu; Fei Mao; Jin Zhu; Xu Shen; Jian Li (Elsevier, 2020)
Drug repurposing is an efficient strategy for new drug discovery. Our latest study found that nitazoxanide (NTZ), an approved anti-parasite drug, was an autophagy activator and could alleviate the symptom of Alzheimer's disease (AD). In order to further improve the efficacy and discover new chemical entities, a series of NTZ-based derivatives were designed, synthesized, and evaluated as autophagy activator against AD. All compounds were screened by the inhibition of phosphorylation of p70S6K, which was the direct substrate of mammalian target of rapamycin (mTOR) and its phosphorylation level could reflect the mTOR-dependent autophagy level. Among these analogs, compound 22 exhibited excellent potency in promoting β-amyloid (Aβ) clearance, inhibiting tau phosphorylation, as well as stimulating autophagy both in vitro and in vivo. What's more, 22 could effectively improve the memory and cognitive impairments in APP/PS1 transgenic AD model mice. These results demonstrated that 22 was a potential candidate for the treatment of AD. Key words: Alzheimer's disease, Autophagy, Nitazoxanide, β-amyloid, Tau protein